Admission Random Blood Glucose, Fasting Blood Glucose, Stress Hyperglycemia Ratio, and Functional Outcomes in Patients With Acute Ischemic Stroke Treated With Intravenous Thrombolysis - Chen, Guangyong; Ren, Junli; Huang, Honghao; Shen, Jiamin; Yang, Chenguang; Hu, Jingyu; Pan, Wenjing; Sun, Fangyue; Zhou, Xinbo; Zeng, Tian; Li, Shengqi; Yang, Dehao; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Stress hyperglycemia ratio (SHR), calculated as glucose/glycated hemoglobin, has recently been developed for assessing stress hyperglycemia and could provide prognostic information for various disease. However, calculating SHR using random blood glucose (RBG) drawn on admission or fasting blood glucose (FBG) could lead to different results. The present study intended to evaluate the association between SHR and function outcomes in acute ischemic stroke (AIS) patients with recombinant tissue plasminogen activator (r-tPA) intravenous thrombolysis. Methods: Data from 230 AIS patients following thrombolytic therapy with r-tPA in the Third Affiliated Hospital of Wenzhou Medical University from Apr. 2016 to Apr. 2019 were retrospectively reviewed. SHR1 was defined as [RBG (mmol/L)]/[HbA1c (%)] and SHR2 was defined as [FBG (mmol/L)]/[HbA1c(%)]. The outcomes included early neurological improvement (ENI), poor function defined as modified Rankin Scale score (mRS) of 3 to 6 and all-cause death at 3-month. Multivariable logistic regression was performed to estimate the association between SHR and adverse outcomes. Results: After adjustment for possible confounders, though AIS patients with higher SHR1 tend to have higher risk of poor outcome and death and unlikely to develop ENI, these didn’t reach the statistical significance. In contrast, SHR2 was independently associated with the poor function outcome (per 0.1-point increases: OR = 1.383 95%CI [1.147-1.668]). Further adjusted for body mass index (BMI), triglyceride-glucose index (TyG), and diabetes slightly strengthen the association between SHR (both 1 and 2) and adverse outcomes. In subgroup analyze, elevated SHR1 is associated with poor function outcomes (per 0.1-point increases: OR = 1.246 95%CI [1.041-1.492]) in non-diabetes individuals and the association between SHR2 and the poor outcomes were attenuated in non-cardioembolic AIS. Conclusion: SHR is expected to replace random or fasting glucose concentration as a novel generation of prognostic indicator and a potential therapeutic target. Keywords: Random Blood glucose, Fasting Blood Glucose, Stress Hyperglycemia Ratio, Stroke, Intravenous Thrombolysis